Comparative Transcriptomic Profiling of Pellicle and Planktonic Cells from Carbapenem-Resistant Acinetobacter baumannii - Heng Kang Ng; Suat Moi Puah; Cindy Shuan Ju Teh; Nuryana Idris; Kek Heng Chua (MDPI AG, 2023)
Acinetobacter baumannii forms air-liquid interface pellicles that boost its ability to withstand desiccation and increase survival under antibiotic pressure. This study aims to delve into the transcriptomic profiles of pellicle cells from clinical strains of carbapenem-resistant A. baumannii (CRAB). The total RNA was extracted from pellicle cells from three pellicle-forming CRAB strains and planktonic cells from three non-pellicle-forming CRAB strains, subject to RNA sequencing using Illumina HiSeq 2500 system. A transcriptomic analysis between pellicle and planktonic cells, along with differential expression genes (DEGs) analysis and enrichment analysis of annotated COGs, GOs, and KEGGs, was performed. Our analysis identified 366 DEGs in pellicle cells: 162 upregulated genes and 204 downregulated genes. The upregulated ABUW_1624 (yiaY) gene and downregulated ABUW_1550 gene indicated potential involvement in fatty acid degradation during pellicle formation. Another upregulated ABUW_2820 (metQ) gene, encoding the D-methionine transporter system, hinted at its contribution to pellicle formation. The upregulation of two-component systems, CusSR and KdpDE, which implies the regulation of copper and potassium ions in a CRAB pellicle formation was also observed. These findings provide valuable insights into the regulation of gene expression during the formation of pellicles in CRAB, and these are potential targets that may aid in the eradication of CRAB infections.